Falkland Islands War, A Selected Bibliography. - ARMY WAR COLL CARLISLE BARRACKS PA (1984)
This selected and annotated bibliography represents a beginning for the student of contingency planning and its application in the Falklands Campaign. The listings in this bibliography will be available during the period of Course 8 (Application of Power: Contingency Planning) in the Library Reserve Room. This bibliography is not intended to be comprehensive but rather represents a summary of the more useful holdings found in the U.S. Army war College Library. The serious scholar will surely wish to go well beyond this bibliography in further research. Additional information and assistance may be obtained from the Library Services Branch, U.S. Army War College, AUTOVON 242-3660 or (717) 245-3660.